High temperature induces investment in phloem and increases sucrose accumulation in grapevine - Wolberg, Shunamit; Dumbur, Rita; Netzer, Yishai; Grünzweig, José M.; Shtein, Ilana (Trees (Berlin, West), 2024)
There’s a lack of studies on the structure–function aspect of linking non-structural carbohydrates to temperature, in particular phloem structure is yet a largely neglected subject. We studied gas exchange parameters and in parallel examined functional anatomy and non-structural carbohydrates status in leaf blades, petioles and branches in ‘Cabernet Sauvignon’ grapevines grown under three temperature regimes (22/16 °C, 28/22 °C, 34/28 °C day/night). After  two months of growth, water use efficiency was the highest at 34 ºC. The individual organs size became progressively smaller as the temperatures increased, and was the smallest at 34 ºC for branch and petiole diameter, and for leaf thickness. The relative xylem cross-sectional area was largely not influenced by the temperature regime. In contrast, phloem cross-sectional area was significantly increased at high temperature in branches and petioles, and became 30% higher at 34 ºC in branches compared to 22 °C. The leaves had the highest non-structural carbohydrates concentration compared to petioles and branches. Sucrose content exhibited a temperature-dependent increase both in branches and petioles, and to some extent also in leaves, while starch, fructose and glucose content did not exhibit any statistically significant temperature trends. In grapevine, sucrose is the main non-structural carbohydrate used for long-distance transport. Our results indicate temperature dependent increased investment in phloem development in parallel with increased main long-distance transported sugar (sucrose) accumulation. Phloem and xylem development were apparently uncoupled, implying a differential cambium activity for each tissue. Our study could have wide structural–functional implications in the ongoing climate change scenario.